Effects of fruit‐baited trap height on flower and leaf chafer scarab beetles sampling in Amazon rainforest. Issue 3 (19th May 2020) - Puker, Anderson; Correa, César M. A.; Silva, Adriano S.; Silva, João V. O.; Korasaki, Vanesca; Grossi, Paschoal C.
Abstract: There is no standardization of ideal trap installation height for an accurate sampling of flower and leaf chafer scarab beetles in the rainforest canopy. This limits the comparison among different studies on the ecology as well as systematic collecting of this beetle group. Here, we sampled flower and leaf chafer beetles using fruit‐baited traps installed at different heights (1.5, 4.5, 7.5 and 10.5 m) in the Brazilian Amazon rainforest with the following proposals: (i) we tested whether there are effects of trap installation height on the abundance, species richness and biomass of these beetles; and (ii) we tested whether there is a difference in the species composition between each trap height. From January to April 2017, we sampled flower and leaf chafer beetles by using traps baited with a banana and sugarcane juice mixture in Amazon rainforest fragments in Porto Velho, Rondônia, Brazil. The abundance, species richness and biomass of flower chafer beetles (Cetoniinae) were higher in traps installed at 10.5 m. For leaf chafer beetles (Rutelinae), we found the higher species richness and abundance at 4.5, 7.5 and 10.5 m, but the biomass of these insects did not differ among the different heights. Only the community composition of flower chafer beetles differed among the different trap installation heights. Our results showed that flower chafer beetles demonstrate a preference for foraging for resources at greater heights in the Amazon rainforest. Thus, to collect cetoniines from tropical forests, the recommended manner is to install the traps in the forest canopy. Abstract : Until now, there has been very little information on scarab beetle biodiversity (Coleoptera: Scarabaeoidea) in the canopy of tropical forests in the Neotropical region. In this study, we sampled flower and leaf chafer beetles using fruit‐baited traps installed at different heights (1.5, 4.5, 7.5 and 10.5 m above ground) in the Brazilian Amazon rainforest. We showed that flower chafer beetles (Cetoniinae) demonstrate a preference for foraging for resources at greater heights in the Amazon rainforest. Thus, to collect cetoniines from tropical forests, the recommended manner is to install the traps in the forest canopy.